MODEL EKONOMI BERBAGI â€œMobile-SECOâ€ (PLATFORM MULTI-SIDED MARKETS) SEBAGAI EKOSISTEM SOSIO-EKONOMI ISLAMI - Maika, M. Ruslianor (Fakultas Ekonomi, UIN Maliki Malang, 2016)
The most disruptive business model innovation of 21st century global market place is sharingeconomy. The value of sharing is indispensable to unlocking ambiguity, paradox and the uncertainty ofeconomy. Sharing economy by definition has to design socio-economic ecosystem between communitieswho share features of production. Sharing economy hold three core features: (1) digital platform, (2) access ofownership and (3) deeper social interaction. Mobile SECO will comes as a platform of multi-sided marketswhich aims to developers capturing value of socio-economic ecosystem. With that value, Mobile-SECO willhelps users and developer campaign the project to be shared with all of social media, thatâ€™s what we call Mini-Campaign Platform (MCP). Hopefully, Mobile-SECO will become a platform that can attract developers toimplement of fiqh muamalah as community service obligations.